(untitled) (Swiss Medical Weekly, 2021)
BACKGROUND: All over the world, patients die while waiting for a transplant. Facing this difficulty, countries struggle to find efficient procedures and policies. One policy that has recently been enforced in many countries is the presumed consent (opt-out) system for organ donation. In such a system, every individual is considered as a potential organ donor except in cases of expressed refusal during her or his lifetime. Based on the input of a citizen’s initiative, the Swiss parliament has made a proposal for a soft presumed consent policy.It was accepted by both chambers at the national level, but will possibly be challenged by a referendum, and give rise to a public vote. OBJECTIVE: Ahead of the democratic debate, our aim was to sound out what issues are perceived as relevant by ordinary citizens when they evaluate different policies regulating organ donation. What are their main worries and decision criteria? METHODS: We conducted semi-structured taped interviews with ordinary citizens during which we asked their views on three different systems: the current opt-in system, the opt-out presumed consent system described in a soft and in a hard version, and the mandatory decision system. We analysed transcripts by coding, and grouping code families up to four levels. We achieved saturation with fifteenth interviews. RESULTS: All our participants happened to be favourably disposed towards organ donation. Participants considered it important to choose a policy that contributes to overcoming the current shortage of organs, but not by any means. They were mostly concerned about individual rights and liberties, and more specifically about the importance of respecting the deceased’s will and to promote lifetime advanced directives on organ donation. The role and rights of relatives were recurrent topics on which participants expressed divergent opinions. Participants often concluded that no legal system is perfect and spent much time discussing elements that were relevant to organ donation in general but not specifically linked to a given legal system. CONCLUSION: This study provides useful information about citizens’ concerns regarding organ donation. In preparation of public debates on an opt-out policy, our results reveal what issues are likely to tilt the public opinion.